Exceptions to Agreements on Intellectual Property Rights in Business Competition Law in the Field of Technology Innovation - Kartiko, Galuh (Nursyam Centre, 2023)
This article aims to shows that economic strength is the main foundation of a country in any part of the world; meaning that it has the same sovereignty as other countries. To achieve this, synergy between the government and the community is needed in building political will related to economic management. The state is the party that has the authority to establish ground rules that support and protect economic activity and growth. Qualitative research using literature methods or secondary legal materials, journals, and also taking from primary legal materials, namely related laws. The result of this research is the current era, technological innovation does not just stop at producing new products or services. However, in this era, technological innovation has had a negative impact on the development of existing businesses, where the presence of technological innovation has disrupted conventional business. Conditions like this by Christensen call disruptive innovation. So, there are several legal and economic problems arising from the phenomenon. In particular, an interesting legal issue in the context of the phenomenon of disruptive innovation is related to intellectual property rights